2021
DOI: 10.3390/f12060728
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Affects Forest Fires: The Impact of Anthropogenic Factors on the Density of Forest Fires in Poland

Abstract: Forest fires, due to climate change, are a growing threat to human life, health, and property, especially in temperate climates. Unfortunately, the impact of individual factors on forest fires varies, depending on the geographical region and its natural and socio-economic conditions. The latter are rarely introduced into fire warning systems, which significantly reduces their effectiveness. Therefore, the main goal of this study was to quantify the impact of a wide range of anthropogenic factors on forest fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Anthropogenic factors that cause increases in fire probability are inextricably linked to human activities in forested areas (Kolanek et al 2021). These factors include agricultural, recreational, and manufacturing activities and result in constant pressure on the forest ecosystem (Kolanek et al 2021). Our study has shown that population density, distance from buildings, railways and roads are particularly important anthropogenic factors that determine the probability of fire.…”
Section: Relationships Between Human Factors and Occurrence Of Forest...mentioning
confidence: 85%
See 4 more Smart Citations
“…Anthropogenic factors that cause increases in fire probability are inextricably linked to human activities in forested areas (Kolanek et al 2021). These factors include agricultural, recreational, and manufacturing activities and result in constant pressure on the forest ecosystem (Kolanek et al 2021). Our study has shown that population density, distance from buildings, railways and roads are particularly important anthropogenic factors that determine the probability of fire.…”
Section: Relationships Between Human Factors and Occurrence Of Forest...mentioning
confidence: 85%
“…Anthropogenic factors that cause increases in fire probability are inextricably linked to human activities in forested areas (Kolanek et al 2021). These factors include agricultural, recreational, and manufacturing activities and result in constant pressure on the forest ecosystem (Kolanek et al 2021).…”
Section: Relationships Between Human Factors and Occurrence Of Forest...mentioning
confidence: 99%
See 3 more Smart Citations